Implementation and assessment of a novel non-clinical skills curriculum for urology residents - Sheetz, Tyler; Diab, Dinah; Scimeca, Alicia; Bellows, Fara; Sharp, David S.; Lee, Cheryl T.; Posid, Tasha (Frontiers in Urology, 2023)
Background: Urology is an increasingly competitive specialty that procures a highly selected and clinically excellent cohort of residents. However, other training needs such as leadership and professional development go underrecognized despite an identified need for formal training in these areas. The aim of this study was to implement, evaluate, and pilot a non-clinical skills curriculum, a novel individualized professional development workshop series, at a single institution. Methods: Eighteen urology residents (15/year, 3 graduates/year) participated in this study over the course of two academic years. A pre-curriculum needs assessment was completed by 15 residents in Year 1 for purposes of curriculum design. The curriculum itself was a series of 1-hour monthly workshops given by an expert speaker on topics relevant to healthcare delivery, leadership and career promotion across various contexts. Survey-based assessments tracked gains in subject knowledge and satisfaction via a pre-post test design. Results: The pre-curriculum needs assessment indicated that trainees desired additional instruction in non-clinical skills (ps>0.1) and endorsed formal teaching to ensure success in their future careers (p<0.001). Trainees reported pre- to post-curriculum gains across each individual learning topic (Mean=20%, p<0.001) with an aggregate increase in subject knowledge of 17% for senior residents and 21% for junior residents (p<0.001). Conclusions: A non-clinical skills curriculum implemented as a pilot ‘Hidden Curriculum’ for urology trainees was feasible and resulted in significant gains in non-clinical subject knowledge. Workshops were highly rated and trainees reported high satisfaction with the curriculum.